Chemical constituents variations of essential oils from rhizomes of four Zingiberaceae species - Md. Sukari, Mohd Aspollah; Mohd Sharif, Nurul Waznah; Yap, Amy Li Ching; Tang, Sook Wah; Neoh, Bee Keat; Rahmani, Mawardi; Ee, Gwendoline Cheng Lian; Yap, Taufiq Yun Hin; Yusuf, Umi Kalsom (Malaysian Analytical Sciences Society, 2008)
The essential oils were extracted using the hydrodistillation method from four ZingibeZingiber amaricans, Kaempferia galanga, and Boesenbergia pandurata were identified as E-citral (20.98%), zerumbone (40.70%), ethyl p-methoxycinnamate (58.47%) and camphor (57.97%), respectively. Kaempferia galanga and Zingiber amaricans were rich in sesquiterpenes whereas Boesenbergia pandurata and Zingiber officinale var. rubrum contained mostly monoterpenes.